Multiband Switchable Terahertz Quarter-Wave Plates via Phase-Change Metasurfaces - Dacheng Wang; Lingchao Zhang; Yandong Gong; Linke Jian; T. Venkatesan; Cheng-Wei Qiu; Minghui Hong (IEEE Photonics Journal, 2016)
Metasurfaces open up a low-dimensional artificial approach to tailor electromagnetic (EM) waves with unprecedented functionalities. However, the ability to actively control and manipulate EM waves via metasurfaces still faces challenges that need to be overcome. Here, we experimentally demonstrated a multiband switchable terahertz quarter-wave plate via inserting a phase-change material, i.e., vanadium dioxide (VO 2), into complementary electric split-ring resonators. Before the VO 2 phase transition, this phase-change metasurface achieves linear-to-circular polarization conversion at 0.45 and 1.10 THz with an ellipticity of 0.998 and $-$ 0.971, respectively. After the VO 2 phase transition, linear-to-circular polarization conversion is obtained at both 0.50 and 1.05 THz with an ellipticity of 0.999 and $-$ 0.999, respectively. This work reveals the feasibility of using phase-change metasurfaces for multiband tunable active terahertz polarization control, and such compact tunable devices can be designed for other frequency regimes as well.